Small Differences in Diet Facilitate the Coexistence of Three Forage Fish Species in an Inshore Northern Patagonian Habitat - Wiesebron, Lauren E.; Castro, Leonardo R.; Soto, Samuel; Castillo, Jorge (Frontiers in Marine Science, 2022)
Forage fish play the crucial role of transferring energy from lower to upper trophic levels. These small pelagic fish feed on plankton and can compete with each other for food, leading to potentially complex interactions. Three forage fish species (Sprattus fuegensis, Strangomera bentincki, and Engraulis ringens) are commonly found in the inshore waters of Northern Chilean Patagonia, a region with large spatial variability in oceanographic conditions and in the zooplankton community. To better understand what factors may explain coexistence among these three forage fish species, we examined differences in resource availability (zooplankton community and abundances) in three locations (Chiloé, Cordillera and Aysén regions) within Northern Patagonia. We compared the diet of the three fish species using both stable isotope and stomach content analyses, and we measured their gill rakers. S. fuegensis, the only species found in all three regions, had flexible diets which lent it greater success than the other two species at foraging in waters with fewer prey. We found little diet differentiation among the three species in the copepod-rich Cordillera region, but the diverging diets of S. bentincki and S. fuegensis in the copepod-poor Chiloé region suggest that diet partitioning in areas with fewer resources is due to competition. The small differences in diet facilitates coexistence among the three species, which may help explain the lack of correlation between the three species’ population abundances in the Cordillera region over the past six years. Finally, our results show that the high degree of oceanographic heterogeneity in Northern Patagonia may encourage species separation based on their specific environmental requirements.